Identifying, Building and Sustaining Leadership Capacity for Communities of Practice in Higher Education : Final Report. - McDonald, Jacquelin; Star, Cassandra; Margetts, Fiona (Office for Learning and Teaching, 2012)
Final report from a project that focused on building the leadership capacity of facilitators of communities of practice (CoPs) for learning and teaching. Research into leadership in its various forms in higher education has focused on formal programs for professional development and yet has identified, at best, tenuous links between such programs and student learning outcomes. CoPs provide a context for academics to engage in supportive and sustained learning situated in their teaching practice. However, for such communities to be successful, they need to develop informal leadership structures, often unsupported by the institution, and foster leadership skills that effectively meet the needs of teaching academics, while negotiating the institutional leadership terrain. An increasing body of current literature suggests that well-led and structured CoPs are successful in leading change and transforming teaching and learning practice, but there has been little attention to the leadership needs of these groups in the higher education context.